Method for measuring the crystallinity of polyacrylonitrile filaments

CN117849106BActive Publication Date: 2026-10-27ZHONGFU SHENYING CARBON FIBER
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410136698.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-31
Publication Date
2026-10-27
Estimated Expiration
2044-01-31

AI Technical Summary

Technical Problem

然而,XRD设备较为昂贵,限制了其广泛应用

Benefits of technology

[0031]本申请提供的技术方案可以包括以下有益效果:本申请通过建立热量比值-非晶区含量对应关系曲线,可以快速、准确地测量出聚丙烯腈原丝的结晶度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117849106B_ABST
    Figure CN117849106B_ABST
Patent Text Reader

Abstract

This application provides a method for measuring the crystallinity of polyacrylonitrile precursor fibers, belonging to the field of carbon fiber production measurement technology. The method includes: determining the heat ratio H0 of the target polyacrylonitrile precursor fiber; determining the amorphous region content W0 of the target polyacrylonitrile precursor fiber based on the heat ratio H0 and the heat ratio-amorphous region content correlation curve; and, based on the amorphous region content W0 of the target polyacrylonitrile precursor fiber, calculating the crystallinity according to formula X... C0 =100% - W0, calculate the crystallinity X of the target polyacrylonitrile precursor fiber. C0 This application establishes a curve showing the relationship between the heat ratio and the content of amorphous regions, which allows for the rapid and accurate measurement of the crystallinity of polyacrylonitrile precursor fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of carbon fiber production measurement technology, and in particular relates to a method for measuring the crystallinity of polyacrylonitrile precursor fibers. Background Technology

[0002] Polyacrylonitrile-based carbon fiber (PAN-CF) is produced by carbonizing polyacrylonitrile (PAN) precursor fibers. Therefore, the preparation of high-quality PAN precursor fibers is a key technology in the research and development of high-performance PAN-based carbon fibers. PAN precursor fibers are semi-crystalline polymers, and crystallinity is one of the important structural parameters of PAN precursor fibers. The crystallinity of PAN precursor fibers has a significant impact on its pre-oxidation process, thus affecting the performance of CF preparation.

[0003] Currently, the crystallinity of PAN precursor fibers is generally determined using X-ray diffraction (XRD). However, XRD equipment is relatively expensive, limiting its widespread application. Therefore, there is a need to develop a new method for measuring the crystallinity of PAN precursor fibers. Summary of the Invention

[0004] This application provides a method for measuring the crystallinity of polyacrylonitrile precursor fibers, which can quickly and accurately measure the crystallinity of polyacrylonitrile precursor fibers.

[0005] This application discloses a method for measuring the crystallinity of polyacrylonitrile precursor fibers, comprising:

[0006] The heat ratio H0 of the target polyacrylonitrile precursor fiber was determined.

[0007] Based on the heat ratio H0 of the target polyacrylonitrile precursor and the corresponding curve of heat ratio-amorphous region content, the amorphous region content W0 of the target polyacrylonitrile precursor is determined.

[0008] Based on the amorphous region content W0 of the target polyacrylonitrile precursor fiber, according to formula X C0 =100% - W0, the crystallinity X of the target polyacrylonitrile precursor fiber is calculated. C0 .

[0009] In some embodiments of this application, the determination of the heat ratio H0 of the target polyacrylonitrile precursor fiber includes:

[0010] Two identical samples were taken from the target polyacrylonitrile precursor fiber to be tested, and they were respectively designated as the first target polyacrylonitrile precursor fiber sample and the second target polyacrylonitrile precursor fiber sample.

[0011] The first target polyacrylonitrile precursor sample is heated from the first preset temperature to the second preset temperature at the first preset heating rate, and the heat release H'0 is recorded.

[0012] The second target polyacrylonitrile precursor sample is heated from the first preset temperature to the third preset temperature at the first preset heating rate. After being held at the third preset temperature for a preset time, it is heated from the third preset temperature to the second preset temperature at the first preset heating rate, and the heat release H”0 is recorded.

[0013] The heat ratio H0 of the target polyacrylonitrile precursor fiber is calculated according to the formula H0=(H”0-H'0) / H'0.

[0014] In some embodiments of this application, the first preset temperature is 30-100°C, and the second preset temperature is 400-480°C.

[0015] In some embodiments of this application, the third preset temperature is 140–190°C, and the preset duration is 40–100 min.

[0016] In some embodiments of this application, the first preset heating rate is 5 to 30 °C / min.

[0017] In some embodiments of this application, the heat release H'0 and the heat release H”0 are determined by differential scanning calorimetry.

[0018] In some embodiments of this application, the method for determining the curve corresponding to the heat ratio and the amorphous region content includes:

[0019] Select multiple standard polyacrylonitrile precursor fibers with different and known amorphous region contents W;

[0020] The heat ratio H of each standard polyacrylonitrile precursor fiber was measured to obtain the heat ratio H of multiple standard polyacrylonitrile precursor fibers.

[0021] Linear fitting was performed on the data points of the heat ratio H of multiple standard polyacrylonitrile precursor fibers and the amorphous region content W of multiple standard polyacrylonitrile precursor fibers to obtain the corresponding curve of heat ratio-amorphous region content.

[0022] In some embodiments of this application, the selection of multiple standard polyacrylonitrile precursor fibers with known and different amorphous region contents W includes:

[0023] Select multiple crystallinity X C Known standard polyacrylonitrile precursor fibers, among which, the crystallinity X of multiple standard polyacrylonitrile precursor fibers... C It exhibits a gradient distribution;

[0024] According to the formula W = 100% - X C The amorphous region content W of each standard polyacrylonitrile precursor fiber was calculated to obtain the amorphous region content W of multiple standard polyacrylonitrile precursor fibers.

[0025] In some embodiments of this application, the determination of the heat ratio H of each standard polyacrylonitrile precursor fiber includes:

[0026] Two identical samples were taken from the standard polyacrylonitrile precursor fibers to be tested, and they were designated as the first standard polyacrylonitrile precursor fiber sample and the second standard polyacrylonitrile precursor fiber sample to be tested, respectively.

[0027] Each of the first test standard polyacrylonitrile precursor fiber samples is heated from a first preset temperature to a second preset temperature at a first preset heating rate, and the heat release H' is recorded.

[0028] Each of the second test standard polyacrylonitrile precursor fiber samples is heated from the first preset temperature to the third preset temperature at a first preset heating rate, held at the third preset temperature for a preset time, and then heated from the third preset temperature to the second preset temperature at the first preset heating rate. The heat release H” is recorded.

[0029] The heat ratio H of the standard polyacrylonitrile precursor fiber is calculated using the formula H = (H” - H') / H'.

[0030] In some embodiments of this application, the number of standard polyacrylonitrile precursor fibers is 6 to 15.

[0031] The technical solution provided in this application may include the following beneficial effects: By establishing a curve showing the relationship between heat ratio and amorphous region content, this application can quickly and accurately measure the crystallinity of polyacrylonitrile precursor fibers.

[0032] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and do not limit this application. Attached Figure Description

[0033] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0034] Figure 1 This is a flowchart illustrating a method for measuring the crystallinity of polyacrylonitrile precursor fibers according to an exemplary embodiment.

[0035] Figure 2 This is a flowchart illustrating a method for determining the heat ratio of a target polyacrylonitrile precursor fiber according to an exemplary embodiment.

[0036] Figure 3 This is a DSC curve of a target polyacrylonitrile precursor fiber according to an exemplary embodiment.

[0037] Figure 4This is a flowchart illustrating a method for determining the relationship curve between the heat ratio and the content of amorphous regions in a method for measuring the crystallinity of polyacrylonitrile precursor fibers, according to an exemplary embodiment.

[0038] Figure 5 This is a flowchart illustrating a method for selecting a number of standard polyacrylonitrile precursor fibers with different and known amorphous region contents W in a method for measuring the crystallinity of polyacrylonitrile precursor fibers according to an exemplary embodiment.

[0039] Figure 6 This is an XRD pattern of a standard polyacrylonitrile precursor fiber according to an exemplary embodiment.

[0040] Figure 7 This is the curve showing the relationship between the heat ratio and the amorphous region content in Example 1. Detailed Implementation

[0041] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of this application will be clearly and completely described below in conjunction with the embodiments and accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of this application can be arbitrarily combined with each other.

[0042] For polymers, in addition to XRD, differential scanning calorimetry (DSC) can also be used to determine their crystallinity. DSC first measures the heat of fusion (ΔH) of the polymer sample, and then determines the heat of fusion (ΔH) of a fully crystalline sample of the polymer. C ), by calculating ΔH / ΔH C The crystallinity of the polymer sample can be obtained by measuring the ratio of the melting temperature to the melting temperature. However, since the melting temperature of PAN (ca. 320℃) is above its decomposition temperature (ca. 250℃), it begins to decompose before reaching its melting point, making it impossible to accurately measure its heat of fusion. Therefore, the conventional DSC method cannot measure the crystallinity of PAN precursor fibers.

[0043] This application provides a method for measuring the crystallinity of polyacrylonitrile (PA) precursor fibers. By measuring the heat ratio of the target PA precursor fiber, and based on the correlation curve between the heat ratio and the amorphous region content, the amorphous region content of the target PA precursor fiber can be determined. Based on the correlation between the amorphous region content and the crystallinity, the crystallinity of the target PA precursor fiber can be obtained. This method broadens the characterization pathway for the crystallinity of PA precursor fibers and overcomes the difficulty of characterizing the crystallinity of PA precursor fibers using melt DSC.

[0044] In one exemplary embodiment, reference is made to Figure 1 This application provides a method for measuring the crystallinity of polyacrylonitrile precursor fibers, comprising:

[0045] S100, Determine the heat ratio H0 of the target polyacrylonitrile precursor fiber.

[0046] S200. Based on the heat ratio H0 of the target polyacrylonitrile precursor and the corresponding curve of heat ratio-amorphous region content, the amorphous region content W0 of the target polyacrylonitrile precursor is determined.

[0047] S300, based on the amorphous region content W0 of the target polyacrylonitrile precursor fiber, according to formula X C0 =100% - W0, calculate the crystallinity X of the target polyacrylonitrile precursor fiber. C0 .

[0048] This application provides a method for measuring the crystallinity of polyacrylonitrile (PAN) precursor fibers. The basic principle is as follows: when the temperature is below the glass transition temperature (Tg) of PAN, the amorphous molecular chains are "frozen." When the temperature rises above Tg, the molecular chains gain energy and "thaw," and the highly mobile amorphous molecular chains recombine, resulting in "cold crystallization." The degree of cold crystallization can be increased under suitable temperature and sufficient time. The increase in crystallinity brought about by cold crystallization of PAN precursor fibers is reflected by the heat release during the pre-oxidation process (i.e., the heat ratio). Under certain temperature and time conditions, the degree of cold crystallization is positively correlated with the content of amorphous regions in PAN. This application uses the heat ratio of PAN precursor fibers to characterize the degree of cold crystallization. The heat ratio of PAN precursor fibers is correlated with the content of amorphous regions in the PAN precursor fibers to establish a curve showing the relationship between the heat ratio and the amorphous region content. By measuring the heat ratio of the target PAN precursor fiber and combining it with the curve showing the relationship between the heat ratio and the amorphous region content, the amorphous region content W0 of the target PAN precursor fiber can be determined. According to formula X... C0 =100% - W0, calculate the crystallinity X of the target polyacrylonitrile precursor fiber. C0 The method described in this application broadens the characterization pathway for the crystallinity of polyacrylonitrile precursor fibers, overcoming the difficulty of characterizing the crystallinity of polyacrylonitrile precursor fibers using melt DSC.

[0049] In one exemplary embodiment, reference is made to Figure 2 The method for determining the heat ratio H0 of the target polyacrylonitrile precursor fiber in this embodiment is a further explanation of step S100 in the above embodiment, including:

[0050] S110. Take two identical samples from the target polyacrylonitrile precursor fiber to be tested, and designate them as the first target polyacrylonitrile precursor fiber sample and the second target polyacrylonitrile precursor fiber sample, respectively.

[0051] It should be noted that "two identical samples" in step S110 refers to two samples from the same batch whose performance parameters such as crystallinity are exactly the same, or whose performance parameters are slightly different but the difference is within the allowable error limit.

[0052] S120. The first target polyacrylonitrile precursor sample is heated from the first preset temperature to the second preset temperature at the first preset heating rate, and the heat release H'0 is recorded.

[0053] In step S120, when the first target polyacrylonitrile precursor sample is heated from the first preset temperature to the second preset temperature, it will release heat, and the heat released during this process can be recorded as H'0.

[0054] The first preset temperature is much lower than the thermochemical reaction start temperature of the PAN precursor fiber; the second preset temperature is higher than the thermochemical reaction termination temperature of the PAN precursor fiber, but much lower than the temperature of severe thermal decomposition.

[0055] If the first preset temperature is too low (e.g., 0℃), the test will take a long time, and the low-temperature range will be invalid for heat calculation; if the first preset temperature is too high (e.g., 220℃), the pre-oxidation reaction will occur during the process of heating to the first preset temperature, but the heat of reaction will not be included. The second preset temperature is the temperature at which the pre-oxidation reaction is complete; if the second preset temperature is low (e.g., 330℃), the pre-oxidation reaction will not be complete; if the second preset temperature is high (e.g., 500℃), the PAN will undergo a significant pyrolysis reaction, affecting the measurement of the heat of pre-oxidation reaction.

[0056] For example, the first preset temperature is 30 to 100°C, and the second preset temperature is 400 to 480°C.

[0057] Furthermore, the first preset temperature is 30-50℃, and the second preset temperature is 400-450℃.

[0058] For example, the first preset temperature is 30℃, 50℃, 60℃, 80℃ or 100℃.

[0059] The second preset temperature is 400℃, 420℃, 450℃ or 480℃.

[0060] For example, the first preset heating rate is 5 to 30 °C / min.

[0061] Furthermore, the first preset heating rate is 10–20 °C / min.

[0062] For example, the first preset heating rate is 5℃ / min, 10℃ / min, 20℃ / min or 30℃ / min.

[0063] S130. The second target polyacrylonitrile precursor sample is heated from the first preset temperature to the third preset temperature at the first preset heating rate. After being held at the third preset temperature for a preset time, it is heated from the third preset temperature to the second preset temperature at the first preset heating rate, and the heat release H”0 is recorded.

[0064] In step S130, during the process of heating or isothermalizing the second target polyacrylonitrile precursor sample, there are three stages of heat release. The first stage of heat release is the heat released when the second target polyacrylonitrile precursor sample is heated from the first preset temperature to the third preset temperature. The second stage of heat release is the heat released when the second target polyacrylonitrile precursor sample is kept at the third preset temperature for a preset time. The third stage of heat release is the heat released when the second target polyacrylonitrile precursor sample is heated from the third preset temperature to the second preset temperature. The heat release H”0 is the third stage of heat release.

[0065] The starting temperature, ending temperature and heating rate of step S130 are the same as those of step S120. The difference is that step S130 adds an in-situ constant temperature heat treatment section, that is, maintaining a preset time at a third preset temperature.

[0066] The third preset temperature is higher than the glass transition temperature (Tg) of the PAN precursor fiber. When the third preset temperature is above Tg and below the thermochemical reaction temperature, the molecular chains of the amorphous region of PAN are "thawed" and undergo recombination and crystallization.

[0067] The glass transition temperature of the PAN precursor fiber in this application is 120°C. Exemplarily, the third preset temperature is 140–190°C, and the preset duration is 40–100 min.

[0068] Furthermore, the third preset temperature is 160–190℃, and the preset duration is 60–100 min.

[0069] For example, the third preset temperature is 140℃ and the preset duration is 100min.

[0070] Understandably, the third preset temperature and preset duration can also be other values ​​within the above range.

[0071] For example, the third preset temperature is 160℃ and the preset duration is 80min.

[0072] Alternatively, the third preset temperature is 190℃ and the preset duration is 40 minutes.

[0073] S140. Calculate the heat ratio H0 of the target polyacrylonitrile precursor fiber according to the formula H0=(H”0-H'0) / H'0.

[0074] To improve the accuracy of the measurement results, three samples of the target polyacrylonitrile precursor fiber can be taken, and the heat ratio can be measured according to the implementation method in the above embodiments. The average value of the heat ratio is taken as the measured value of the heat ratio of the target polyacrylonitrile precursor fiber.

[0075] In this embodiment, DSC can be used to measure the heat release of the target polyacrylonitrile precursor sample. For example... Figure 3 As shown, Figure 3 This is a DSC curve of the target polyacrylonitrile precursor fiber. The horizontal axis represents temperature (°C), and the vertical axis represents heat flow (mW / mg). The heat release of the target polyacrylonitrile precursor fiber sample is the integral area calculated by the DSC software. In the curve, 1 represents the curve of the first target polyacrylonitrile precursor fiber sample to be tested, and 2 represents the curve of the second target polyacrylonitrile precursor fiber sample to be tested.

[0076] For example, the heat ratio H0 of the target polyacrylonitrile precursor fiber was determined using a differential scanning calorimeter (DSC) in a nitrogen or air atmosphere at a flow rate of 50–100 mL / min.

[0077] Cut the target polyacrylonitrile precursor fiber sample to be tested into pieces, and weigh out two identical samples of 7-10 mg each, which are respectively designated as the first target polyacrylonitrile precursor fiber sample and the second target polyacrylonitrile precursor fiber sample to be tested.

[0078] The heat release H'0 of heating the first target polyacrylonitrile precursor sample from a first preset temperature to a second preset temperature at a first preset heating rate was determined using DSC; wherein, the heat release H'0 can be, for example, […]. Figure 3 The integral area of ​​curve 1 in the figure.

[0079] The heat release H”0 of the second target polyacrylonitrile precursor sample is determined by DSC, which is heated from a first preset temperature to a third preset temperature at a first preset heating rate, held at the third preset temperature for a preset time, and then heated from the third preset temperature to the second preset temperature at the first preset heating rate. The heat release H”0 can be, for example, expressed as H”0. Figure 3 The integral area of ​​curve 2 in the figure.

[0080] The heat ratio H0 of the target polyacrylonitrile precursor fiber is calculated using the formula H0=(H”0-H'0) / H'0.

[0081] Compared to X-ray diffractometers, differential scanning calorimetry (DSC) has the advantage of lower equipment cost. However, current DSC methods are not well-suited for polymers with melting temperatures higher than their decomposition temperatures. Therefore, based on the performance characteristics of PAN, improvements to conventional DSC methods are needed. In related technologies, a swelling agent is used as a reference sample, and PAN plus the swelling agent is used as the experimental sample. The heat difference between the reference and experimental samples during the heating process is taken as the heat absorbed by the dissolution of the PAN condensed-state structure. By segmenting the peaks of the PAN dissolution endothermic curve, the heat contribution of crystalline or amorphous regions can be distinguished, thereby calculating the crystallinity of the PAN sample. This improved method broadens the characterization pathway for the crystallinity of PAN precursor fibers; however, it also presents the problem of easy spillage or decomposition of liquid substances during testing, which can contaminate the instrument's sensors or thermocouples, placing higher demands on the use and maintenance of DSC instruments.

[0082] The method described in this application not only broadens the characterization pathway for the crystallinity of polyacrylonitrile precursor fibers, overcoming the difficulty of characterizing the crystallinity of polyacrylonitrile precursor fibers using fusion DSC, but also reduces contamination and wear on measuring instruments because the measurement method of this application does not require the introduction of liquid reagent samples.

[0083] In one exemplary embodiment, reference is made to Figure 4 The method for determining the heat ratio-amorphous region content correspondence curve in this embodiment is a further explanation of step S200 in the above embodiment, including:

[0084] S210. Select multiple standard polyacrylonitrile precursor fibers with different and known amorphous region contents W.

[0085] In step S210, "multiple" refers to the requirement that the number of standard polyacrylonitrile precursor fibers must be greater than or equal to two. In this embodiment, it is necessary to establish a curve relating the heat ratio to the amorphous region content using standard polyacrylonitrile precursor fibers; therefore, multiple data points are required.

[0086] For example, the number of standard polyacrylonitrile precursor fibers is 6 to 15.

[0087] Furthermore, the number of standard polyacrylonitrile precursor fibers is 6 to 10.

[0088] For example, the number of standard polyacrylonitrile precursor fibers is 6, 8, 10, or 15.

[0089] The phrase "the amorphous region content W differs from one another" in step S210 refers to the differences in the amorphous region content W among multiple standard polyacrylonitrile precursor fibers. In this embodiment, it is necessary to establish a curve relating the heat ratio to the amorphous region content using standard polyacrylonitrile precursor fibers; therefore, multiple different data points are required.

[0090] In step S210, "known" means that the parameters to be characterized in the standard polyacrylonitrile precursor fiber are known. For example, in this embodiment, in order to establish the correlation curve between the heat ratio and the amorphous region content, it is necessary to determine the crystallinity, heat ratio, and amorphous region content of the standard polyacrylonitrile precursor fiber. For example, the amorphous region content W of the standard polyacrylonitrile precursor fiber is determined using conventional X-ray diffraction (XRD).

[0091] S220. Measure the heat ratio H of each standard polyacrylonitrile precursor fiber to obtain the heat ratio H of multiple standard polyacrylonitrile precursor fibers.

[0092] For example, determining the heat ratio H of each standard polyacrylonitrile precursor fiber includes:

[0093] Two identical samples were taken from the standard polyacrylonitrile precursor fibers to be tested, and they were designated as the first standard polyacrylonitrile precursor fiber sample and the second standard polyacrylonitrile precursor fiber sample to be tested, respectively.

[0094] Each first standard polyacrylonitrile precursor sample to be tested is heated from the first preset temperature to the second preset temperature at the first preset heating rate, and the heat release H' is recorded.

[0095] Each second test standard polyacrylonitrile precursor fiber sample is heated from the first preset temperature to the third preset temperature at the first preset heating rate. After being held at the third preset temperature for a preset time, it is heated from the third preset temperature to the second preset temperature at the first preset heating rate, and the heat release H” is recorded.

[0096] The heat ratio H of the standard polyacrylonitrile precursor sample is calculated using the formula H = (H” - H’) / H’.

[0097] S230. Based on the data points of the heat ratio H of multiple standard polyacrylonitrile precursor fibers and the amorphous region content W of multiple standard polyacrylonitrile precursor fibers, a linear fit was performed to obtain the curve of the correspondence between heat ratio and amorphous region content.

[0098] In step S230, a relationship curve corresponding to the heat ratio and amorphous region content is established using data points (H, W) of multiple standard polyacrylonitrile precursor fibers. When measuring the crystallinity of the target polyacrylonitrile precursor fiber, only the heat ratio of the target polyacrylonitrile precursor fiber needs to be measured. Substituting this value into the aforementioned relationship curve, the amorphous region content of the target polyacrylonitrile precursor fiber can be obtained. Then, according to formula X... C0 =100% - W0, which gives the crystallinity of the target polyacrylonitrile precursor fiber.

[0099] In one exemplary embodiment, reference is made to Figure 5This embodiment is a further explanation of step S210 in the above embodiment. In this embodiment, multiple standard polyacrylonitrile precursor fibers with different and known amorphous region contents W are selected, including:

[0100] S211, Select multiple crystallinity X C Known standard polyacrylonitrile precursor fibers, among which, the crystallinity X of multiple standard polyacrylonitrile precursor fibers... C It exhibits a gradient distribution.

[0101] In step S211, the crystallinity of multiple standard polyacrylonitrile precursor fibers with a gradient distribution can be obtained by adjusting the spinning process.

[0102] Crystallinity X of standard polyacrylonitrile precursor fiber C It can be determined using conventional XRD methods. For example... Figure 6 As shown, Figure 6 This is the XRD pattern of a standard polyacrylonitrile precursor fiber. The horizontal axis represents the 2θ diffraction angle in degrees (°), and the vertical axis represents the intensity of the diffraction peaks in counts. H represents the hexagonal phase, and O represents the amorphous phase.

[0103] S212. According to the formula W = 100% - X C The amorphous region content W of each standard polyacrylonitrile precursor fiber was calculated to obtain the amorphous region content W of multiple standard polyacrylonitrile precursor fibers.

[0104] To more clearly explain the technical solution of this application, this application provides specific embodiments of the method for measuring the crystallinity of polyacrylonitrile precursor fibers. The beneficial effects of selecting the above-mentioned ranges of each parameter will be explained through specific experimental data provided in the specific embodiments.

[0105] Example

[0106] Example 1

[0107] A method for measuring the crystallinity of polyacrylonitrile precursor fibers includes the following steps:

[0108] (1) Eight groups of PAN precursor fibers with crystallinity gradients were selected as standard polyacrylonitrile precursor fibers to be tested; the crystallinity of each group of standard polyacrylonitrile precursor fibers to be tested was determined by XRD method to obtain the crystallinity X. C 1……X C The percentages, from smallest to largest, are 41.16%, 43.25%, 45.35%, 47.15%, 48.77%, 49.97%, 50.75%, and 52.09%. According to the formula W = 100% - X... CThe amorphous region contents of the eight standard polyacrylonitrile precursor fibers, W1 to W8, were calculated to be 58.84%, 56.75%, 54.65%, 52.85%, 51.23%, 50.03%, 49.25%, and 47.91%, respectively.

[0109] (2) The standard polyacrylonitrile precursor fibers to be tested were subjected to DSC testing. The test atmosphere was air, and the flow rate was 60 mL / min. The standard polyacrylonitrile precursor fibers to be tested were cut into pieces, and two identical 8 mg samples were weighed out and recorded as the first standard polyacrylonitrile precursor fiber sample and the second standard polyacrylonitrile precursor fiber sample, respectively. The first standard polyacrylonitrile precursor fiber sample was heated from 30 °C to 450 °C at a heating rate of 10 °C / min, and the heat release H' was recorded. The second standard polyacrylonitrile precursor fiber sample was heated from 30 °C to 160 °C at a heating rate of 10 °C / min, held at 160 °C for 60 min, and then heated from 160 °C to 450 °C at a heating rate of 10 °C / min, and the heat release H” was recorded. The heat ratio H of the standard polyacrylonitrile precursor fibers was calculated according to the formula H=(H”-H’) / H’.

[0110] The heat release H' and heat release H” are both calculated as the average of three parallel tests.

[0111] Following the above method, the heat ratios H1…H8 of the eight groups of standard polyacrylonitrile precursor fibers were determined to be 47.79%, 39.20%, 31.52%, 25.23%, 17.48%, 13.8%, 9.89%, and 4.79%, respectively.

[0112] The heat ratio H of eight standard polyacrylonitrile precursor fibers was linearly fitted to the data points (H, W) of amorphous region content W to obtain the following results: Figure 7 The working curve shown has the relationship y = 0.2549x + 46.6450 (Adj.R-Square = 0.9988). Figure 7 In the graph, the horizontal axis represents the heat ratio, in percentage (%); the vertical axis represents the amorphous region content, in percentage (%).

[0113] (3) The heat ratio H0 of the target polyacrylonitrile precursor fiber (referred to as sample 1) was determined to be 7.19%.

[0114] The method for determining the heat ratio H0 of the target polyacrylonitrile precursor fiber is the same as the method for determining the heat ratio H of the standard polyacrylonitrile precursor fiber in step (2), and will not be repeated here.

[0115] Based on the relationship y = 0.2549x + 46.6450 in step (2), the amorphous region content W0 of the target polyacrylonitrile precursor fiber is calculated to be 48.48%.

[0116] According to formula XC0 =100% - W0, calculate the crystallinity X of the target polyacrylonitrile precursor fiber. C0 It is 51.52%.

[0117] To verify the accuracy of the crystallinity of polyacrylonitrile precursor fibers measured using the method of Example 1, the crystallinity of the target polyacrylonitrile precursor fiber sample in Example 1 was measured using conventional XRD, and the result was 51.99%. The deviation (absolute value) between the crystallinity of polyacrylonitrile precursor fibers measured using the method of Example 1 and the crystallinity measured using XRD was calculated to be within 1%. This indicates that the method of Example 1 of this application has high accuracy in measuring the crystallinity of polyacrylonitrile precursor fibers.

[0118] The formula for calculating the deviation in this application is: (crystallinity measured by the example - crystallinity measured by XRD method) / crystallinity measured by XRD method × 100%.

[0119] To verify the broad applicability of Example 1, the crystallinity of different target polyacrylonitrile precursor fibers was measured using the method of Example 1. The target polyacrylonitrile precursor fiber samples were designated as Sample 2# and Sample 3#, respectively. The crystallinity of Sample 2# and Sample 3# was determined using both the method of Example 1 and XRD.

[0120] The crystallinity of sample #2, determined using the method of Example 1, was 46.15%, while the crystallinity of sample #2, determined using XRD, was 46.08%. The relative deviation between the two was 0.15%.

[0121] The crystallinity of sample #3, determined using the method of Example 1, was 47.97%, while the crystallinity of sample #2, determined using XRD, was 47.25%. The relative deviation between the two was 1.50%.

[0122] Therefore, it can be seen that the method of Example 1 of this application can accurately measure the crystallinity of different polyacrylonitrile precursor fibers.

[0123] It should be noted that for PAN precursor fibers with high crystallinity, the number of amorphous molecular chains is relatively small. Under certain heat treatment temperatures and times, the degree of cold crystallization is relatively low, resulting in a relatively small DSC heat ratio. If the DSC heat ratio is less than the instrument testing system error, the established working curve will be inapplicable. Therefore, there is an upper limit to the crystallinity range of PAN measured by the working curve. For the working curve established in Example 1, the instrument testing system error of the DSC heat ratio is 2.5%, so the upper limit of measurable crystallinity is 52.72%. To broaden the upper limit of crystallinity measurement, the third preset temperature can be appropriately increased or the preset time can be extended to enhance the cold crystallization effect. At the same time, interference from possible cyclization or oxidation reactions should be avoided (i.e., the third preset temperature < 200°C).

[0124] To further illustrate the influence of the third preset temperature, preset duration, and other parameters on the measurement results, the crystallinity of polyacrylonitrile precursor fibers was measured according to the methods of Examples 2-16, and the parameters and measurement results of Examples 2-16 are recorded in Table 1.

[0125] It should be noted that, in Examples 2-16, all parameters are the same as in Example 1, except for the parameters listed in Table 1. The target polyacrylonitrile precursor used in Examples 2-16 is sample #1.

[0126] Table 1. Parameters and measurement results for Examples 1-16

[0127]

[0128] Table 1 (continued) Parameters and measurement results of Examples 1-16

[0129]

[0130] The results of Examples 1 to 4 show that the lower the first preset heating rate, the higher the upper limit of crystallinity measurement, but the larger the measurement deviation. The preferred value is 10 to 20 °C / min.

[0131] The results of Examples 1, 5 to 7 show that the higher the first preset temperature, the smaller the upper limit of crystallinity measurement and the lower the measurement deviation. The preferred value is 30 to 100°C.

[0132] The results of Examples 1, 8 to 10 show that the lower the second preset temperature, the smaller the upper limit of crystallinity measurement and the larger the measurement deviation. The preferred value is 400 to 480°C.

[0133] The results of Examples 1, 11 to 13 show that the higher the third preset temperature, the greater the upper limit of crystallinity measurement and the smaller the measurement deviation. The preferred value is 160 to 190°C.

[0134] The results of Examples 1, 14 to 16 show that the longer the preset time, the higher the upper limit of crystallinity measurement and the smaller the measurement deviation. The preferred value is 60 to 100 min.

[0135] A comparison of the results of Examples 11-13 and Examples 14-16 shows that increasing the temperature is more effective than extending the time in increasing the upper limit of crystallinity measurement.

[0136] It should be noted that, in this document, the terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0137] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit it. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.

Claims

1. A method for measuring the crystallinity of polyacrylonitrile precursor fibers, characterized in that, include: Determining the heat ratio of the target polyacrylonitrile precursor fiber H 0; Based on the heat ratio of the target polyacrylonitrile precursor fiber H The amorphous region content of the target polyacrylonitrile precursor fiber is determined by using the curve showing the relationship between the heat ratio and the amorphous region content. W 0; Based on the amorphous region content of the target polyacrylonitrile precursor fiber W 0, according to the formula X C0 =100%- W 0, the crystallinity of the target polyacrylonitrile precursor fiber is calculated. X C0 ; The heat ratio of the target polyacrylonitrile precursor fiber was determined. H 0, including: Two identical samples were taken from the target polyacrylonitrile precursor fiber to be tested, and they were respectively designated as the first target polyacrylonitrile precursor fiber sample and the second target polyacrylonitrile precursor fiber sample. The first target polyacrylonitrile precursor sample was heated from a first preset temperature to a second preset temperature at a first preset heating rate, and the heat released was recorded. H’ 0; The second target polyacrylonitrile precursor sample is heated from the first preset temperature to the third preset temperature at a first preset heating rate. After being held at the third preset temperature for a preset time, it is heated from the third preset temperature to the second preset temperature at the first preset heating rate, and the heat released is recorded. H” 0; According to the formula H 0 = ( H” 0- H’ 0) / H’ 0, the heat ratio of the target polyacrylonitrile precursor fiber is calculated. H 0.

2. The method for measuring the crystallinity of polyacrylonitrile precursor fiber according to claim 1, characterized in that, The first preset temperature is 30~100℃, and the second preset temperature is 400~480℃.

3. The method for measuring the crystallinity of polyacrylonitrile precursor fiber according to claim 1, characterized in that, The third preset temperature is 140~190℃, and the preset duration is 40~100 min.

4. The method for measuring the crystallinity of polyacrylonitrile precursor fiber according to claim 1, characterized in that, The first preset heating rate is 5~30℃ / min.

5. The method for measuring the crystallinity of polyacrylonitrile precursor fiber according to claim 1, characterized in that, The heat release H’ 0 and the heat release H” 0 was determined using differential scanning calorimetry.

6. The method for measuring the crystallinity of polyacrylonitrile precursor fiber according to claim 1, characterized in that, The method for determining the correlation curve between the heat ratio and the amorphous region content includes: Select multiple amorphous region contents W Different and known standard polyacrylonitrile precursor fibers; The heat ratio of each standard polyacrylonitrile precursor fiber was measured separately. H The heat ratios of multiple standard polyacrylonitrile precursor fibers were obtained. H ; Based on the heat ratio of multiple standard polyacrylonitrile precursor fibers H Amorphous region content of multiple standard polyacrylonitrile precursor fibers W Linear fitting was performed on the data points to obtain the curve showing the relationship between the heat ratio and the amorphous region content.

7. The method for measuring the crystallinity of polyacrylonitrile precursor fiber according to claim 6, characterized in that, The selection of multiple amorphous region contents W Different and known standard polyacrylonitrile precursor fibers include: Select multiple crystallinity X C Known standard polyacrylonitrile precursor fibers, among which, the crystallinity of multiple standard polyacrylonitrile precursor fibers... X C It exhibits a gradient distribution; According to the formula W =100%- X C Calculate the amorphous region content of each standard polyacrylonitrile precursor fiber. W The amorphous region content of multiple standard polyacrylonitrile precursor fibers was obtained. W .

8. The method for measuring the crystallinity of polyacrylonitrile precursor fiber according to claim 6, characterized in that, The heat ratio of each standard polyacrylonitrile precursor fiber was determined. H ,include: Two identical samples were taken from the standard polyacrylonitrile precursor fibers to be tested, and they were designated as the first standard polyacrylonitrile precursor fiber sample and the second standard polyacrylonitrile precursor fiber sample to be tested, respectively. Each of the first standard polyacrylonitrile precursor fiber samples to be tested was heated from a first preset temperature to a second preset temperature at a first preset heating rate, and the heat released was recorded. H’ ; Each of the second test standard polyacrylonitrile precursor fiber samples was heated from the first preset temperature to the third preset temperature at a first preset heating rate, held at the third preset temperature for a preset time, and then heated from the third preset temperature to the second preset temperature at the first preset heating rate. The heat released was recorded. H” ; According to the formula H = ( H” - H’ ) / H’ The heat ratio of the standard polyacrylonitrile precursor sample was calculated. H .

9. The method for measuring the crystallinity of polyacrylonitrile precursor fiber according to claim 6, characterized in that, The number of standard polyacrylonitrile precursor fibers is 6 to 15.

Citation Information

Patent Citations

  • Toner for developing electrostatic latent images and production method of the same

    CN102169299A

  • Method for screening extracting agent and testing residual solvent dimethyl sulfoxide in polyacrylonitrile precursor

    CN113758887A